Characterization of a Novel Mitochondrial Ascorbate Transporter From Rat Liver and Potato Mitochondria - Scalera, Vito; Giangregorio, Nicola; De Leonardis, Silvana; Console, Lara; Carulli, Emanuele Salvatore; Tonazzi, Annamaria (Frontiers in Molecular Biosciences, 2018)
The Mitochondrial Ascorbic Acid Transporter (MAT) from both rat liver and potato mitochondria has been reconstituted in proteoliposomes. The protein has a molecular mass in the range of 28-35 kDa and catalyzes saturable, temperature and pH dependent, unidirectional ascorbic acid transport. The transport activity is sodium independent and it is optimal at acidic pH values. It is stimulated by proton gradient, thus supporting that ascorbate is symported with H+. It is efficiently inhibited by the lysine reagent pyridoxal phosphate and it is not affected by inhibitors of other recognized plasma and mitochondrial membranes ascorbate transporters GLUT1(glucose transporter-1) or SVCT2 (sodium-dependent vitamin C transporter-2). Rat protein catalyzes a cooperative ascorbate transport, being involved two binding sites; the measured K0.5 is 1.5 mM. Taking into account the experimental results we propose that the reconstituted ascorbate transporter is not a GLUT or SVCT, , since it shows different biochemical features. Data of potato transporter overlap the mammalian ones, except for the kinetic parameters non experimentally measurable, thus supporting the MAT in plants fulfills the same transport role.